Islamic Civilization in the Digital Era: The Diversity of Muslim Religious Expression in Social Media - Khodafi, Muhammad; Zulaili, Iin Nur; Juma', Juma'; Sa'adah, Sufi Ikrima (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This article studied the development of Islamic civilization in the digital sphere. The discussion aims to portray the diversity of religious expressions in social media. The researchers employed Bourdieu’s concept of religion as a symbol system, this study tried to reveal the historical background and the patterns of religious expression. This research aims to study and understand the phenomenon of Muslim religious expression in internet-based social media The discussion resulted in the findings that Muslim religious expression in social media develops from traditional, modern, liberal, radical, and recently becomes moderate religious expression. This research is quasi-qualitative research using an ethnographic approach. The basis of the analysis is interpretive on the phenomenon of the diversity of religious expressions of the ummah on social media. The result of this research shows that the emergence of religious websites mostly represents these various expressions. These religious websites and the existence of celebrity preachers then lead to the shifting in the pattern from the traditional to the moderate one.